Using Google Classroom to Increase Students Motivation to Learn English at SMP Negeri 1 Limboto Gorontalo - Muziatun Muziatun; Hasanuddin Fatsah; Monalysa Laonga (Ideas Publishing, 2022)
Teachers experiences might restrict their utilization of technology in the classroom, making learning challenging. Teachers must improve learning performance and motivation to overcome learning obstacles, especially when online learning has supplanted traditional teaching method following Covid-19. Therefore, online learning models should be implemented as a new learning style. This research aims to examine this topic, namely the use of Google Classroom to enhance English learning achievement and motivation. The investigation was qualitative and case-based which include observing and documenting the behaviors of students at SMP Negeri 1 Limboto, Gorontalo, Indonesia, in particular eighth-grade students who learn using Google Classroom. The data will be collected through interviews, observations, and documentation. The findings of this research indicated that the use of Google Classroom increases the intrinsic motivation of students, since all of the assessment indicators are over 60 percent. Therefore, this finding indicated that students prefer to learn English by integrating techonology – in this case Google Classroom. This findings then lead to another finding, in which the integrating of Google Classroom during teaching and learning English may increase students learning performance. In this way, online learning has a positive effect on students learning motivations. By the findings of this research, it has also been confirmed that there is a very closed connection between the intrinsic and extrinsic motivations of the students, which is in line with the theories provided (Gonzalez-DeHass, Willems, & Holbein, 2005; Yuan, Wu, Hu, & Lin, 2019)